Application of The Concept of Hifz Al-Din in Shariah Compliant Business Management - Mohammad Normaaruf Abd Hamid; Anas Mohd Yunus (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
A business that adheres to Islamic law is a business that operates with honesty and not doing any form of prohibited things in Islam. Maqasid Shariah is the basic standard for mankind in doing something towards creating a Shariah-compliant way of life, including in business. Religion is the main aspect that must be emphasized in performing business. Islam is a religion that must be preserved, maintained and expanded by all Muslims. Islam strongly encourages Muslims to get involved in all sort of business, to earn a living and improved livelihoods to mankind, as long as it meets the Quran and al-Sunnah’s standards. Hifz al-Dīn concept is still not taken seriously in a business management. The issues related to religion, such as riba, employees not performing obligatory prayers and unethical attire are still not stress seriously in business operations. Thus, hifz al-Dīn is an important concept in making sure the business carried out complies with the requirements of Islamic legislation. The purpose of this article is to give exposure in implementing hifz al-Dīn concept. This article studies use qualitative methods by using content analysis of materials related to Islamic Maqasid and businesses. As a result, performing obligatory prayers, trades of halal products, shariah compliant dress code and Islamic financial management need to be taken seriously in every business operations in order to make sure it is in line with the requirements of Islamic law based on hifz al-Dīn concept. Abstrak Perniagaan yang mematuhi syariat Islam adalah perniagaan yang dijalankan dengan jujur dan yang tidak melakukan perkara-perkara yang dilarang dalam Islam. Maqasid Shariah adalah piawaian asas bagi manusia dalam melakukan sesuatu dalam mewujudkan cara hidup patuh Syariah, termasuk dalam perniagaan. Agama merupakan aspek utama yang mesti dititikberatkan dalam menjalankan perniagaan. Agama Islam mesti dipelihara dan dikembangkan oleh semua umat Islam. Islam amat menggalakkan umatnya untuk terlibat dalam perniagaan untuk mencari nafkah dan menambah rezeki dengan mesti berlandaskan Al-Quran dan al-Sunnah. Konsep Hifz al-Dīn masih tidak dititikberatkan dalam pengurusan perniagaan. Isu yang berkaitan dengan agama Islam seperti riba, pekerja yang tidak menunaikan ibadah dan pakaian yang tidak beretika masih tidak diberi perhatian yang serius dalam menjalankan perniagaan. Oleh itu, hifz al-Dīn adalah konsep penting dalam memastikan perniagaan yang dijalankan mematuhi kehendak dan ketetapan syariat Islam. Tujuan artikel ini adalah untuk memberi pendedahan dalam melaksanakan konsep hifz al-Dīn. Kajian artikel ini menggunakan kaedah kualitatif dengan menggunakan analisis kandungan bahan yang berkaitan dengan Maqasid Islam dan perniagaan. Rumusannya, kewajipan menunaikan ibadah, pemilihan dan penjualan produk halal, etika berpakaian patuh syariah dan pengurusan kewangan Islam perlu diberi perhatian serius dalam setiap operasi perniagaan dijalankan bagi memastikan perlaksanaannya bertetapan dengan kehendak syariat Islam yang memenuhi konsep hifz al-Dīn. DOI: https://doi.org/10.5281/zenodo.4033019